Thrill Of Le Tour Curtain Raiser - The Star, Ng Wei Loon (2008)
Cycling enthusiasts felt the pulse and share excitement of the 13th edition of the Le Tour de Langkawi (LTdL) at the Kayuhan LTdL08 held in front of the Palace of justice in Putrajaya on Sunday